Queensferry Crossing, UK: towers, piers and abutments – design and construction. Issue 2 (16th July 2018) - Romberg, Martin; Brunton, Kevin; Castro, Jaime Wilson; Moloney, Anne; Robinson, Neil; Wheeler, Mel
Abstract : The new Queensferry Crossing near Edinburgh in Scotland, UK, is a cable-stayed bridge with a total length of 2637·5 m and three towers up to 210 m high. The two cable-supported main spans are 650 m long, the two back spans are 223 m long and there are approach viaducts at each end, with variable spans up to 104 m. The two cable planes are arranged centrally between both carriageways and overlap in the centre of the main spans. This special feature is necessary in order to stabilise the deck and, especially, the central tower. Unique design features such as the world's longest pair of free-standing cantilevers with an overall length of 644 m and constructing the works in an exposed location experiencing adverse weather conditions put very high demands on the engineers and workers involved. This paper describes the design and construction of the substructures compromising three towers, hold-down piers, approach piers and abutments.